Low-level atmospheric ozone exposure induces protection against Botrytis cinerea with down-regulation of ethylene-, jasmonate- and pathogenesis-related genes in tomato fruit - Tzortzakis, Nikos G.; Taybi, Tahar; Roberts, Raveenia; Singleton, Ian; Borland, Anne M.; Barnes, Jeremy D. (My University, 2011)
The aim of this study was to determine if ozone exposure could prevent spoilage in tomato fruit by fungal infection and to explore concomitant changes in expression of genes involved in signal transduction (ethylene, jasmonic acid and C6-aldehydes) and defence-related (chitinases, glucanases and defensin) pathways. Tomato fruit (Lycopersicon esculentum Mill. cv. Mareta) were exposed to low-level ozone enrichment (0.05μmolmol-1) for up to 6 days and then wounded and/or inoculated with Botrytis cinerea (grey mould) and transferred for one or two weeks' post-fumigation exposure to 'clean' (i.e. Charcoal/Purafil®-filtered) air in chilled storage (13°C). Control fruit were maintained throughout in 'clean' air. Pre-exposure to ozone resulted in a marked reduction in lesion development when fruit were subsequently wounded and inoculated with a mycelial plug. Tomato fruit subjected to ozone-enrichment not only showed enhanced protection against fungal infection, but also retained firmness in comparison with fruit maintained in 'clean' air. Ozone treatment resulted in strong inhibition of expression of both signal transduction (1-aminocyclopropane-1-carboxylic acid oxidase, allene oxide synthase and hydroperoxide lyase), and defence-related (acidic chitinase, basic chitinase, acidic glucanase, basic glucanase, plant defensin) genes, and the pattern of change was consistent with suppression of fungal growth. Overall, ozone exposure would appear to enhance tomato resistance to B. cinerea infection and has potential commercial applications. © 2011 Elsevier B.V.
Keywords: Botrytis cinerea; Gene expression; Induced resistance; Microbial spoilage; Ozone; Tomato